Multivariable Chain Rule – Proving an equation of partial derivatives – Exercise 6467


Given the differentiable function


Prove the equation

z''_{xx}\cdot z''_{yy}={(z''_{xy})}^2


We will use the chain rule to calculate the partial derivatives of z.

z'_x=\frac{1}{e^x+e^y}\cdot e^x=


z'_y=\frac{1}{e^x+e^y}\cdot e^y=


We will calculate the second order derivatives.

z''_{xx}=\frac{e^x(e^x+e^y)-e^x\cdot e^x}{{(e^x+e^y)}^2}=

=\frac{e^x\cdot e^y}{{(e^x+e^y)}^2}

z''_{yy}=\frac{e^y(e^x+e^y)-e^y\cdot e^y}{{(e^x+e^y)}^2}=

=\frac{e^y\cdot e^x}{{(e^x+e^y)}^2}

z''_{xy}=\frac{-e^x\cdot e^y}{{(e^x+e^y)}^2}

We will put the partial derivatives in the left side of the equation we need to prove.

z''_{xx}\cdot z''_{yy}=

=\frac{e^x\cdot e^y}{{(e^x+e^y)}^2}\cdot \frac{e^y\cdot e^x}{{(e^x+e^y)}^2}=

=\frac{e^{2x}\cdot e^{2y}}{{(e^x+e^y)}^4}=

={(\frac{e^{x}\cdot e^{y}}{{(e^x+e^y)}^2})}^2=


We got to the right side as required.

Have a question? Found a mistake? – Write a comment below!
Was it helpful? You can buy me a cup of coffee here, which will make me very happy and will help me upload more solutions! 

Share with Friends

Leave a Reply